Indonesian EFL Learners’ Perceptions of ChatGPT’s Translation Readability in Translating English Literary Text - Luqman Rosyidy; Anam Sutopo; Dwi Haryanti (Tell : Teaching of English Language and Literature Journal, 2025)
This study investigated how English as foreign language (EFL) learners in a literary community setting perceived the readability of ChatGPT’s translations in translating an English short story into Indonesian. This research used a short story written by Gerald Murnane entitled The Boy’s Name was David. By using a descriptive qualitative approach, the research explored two questions: the readability score of the translations and learners’ perceptions of this readability. Purposive sampling was employed by involving 18 EFL learners from Kurvadot Creative, a literature discussion community in Cepu, Indonesia. The data were collected through document, questionnaires, and focus group discussions. The readability assessment was analyzed by using Nababan’s Translation Quality Assessment (TQA) framework, while the EFL learners’ perceptions in the discussion was analyzed by using thematic analysis. The results revealed that learners generally rated the ChatGPT translations as Readable, with an average score of 2.68. However, the participants also identified several challenges. These included linguistic issues, such as issues with syntax, semantics, and stylistics, as well as reading engagement problems where the participants required more time to read certain parts of the translation. In addition, the untranslated sentences caused by ChatGPT's content policy restrictions added to the challenges. Despite the relatively high readability ratings, these factors disrupted participants' overall reading experiences with the translated short story by ChatGPT.